Do interactions between patients' psychological distress and adherence to dietary recommendation predict glycemic control among persons with type 2 diabetes in Ghana? - Be‐Ikuu Dominic Doglikuu; Abubakari Abdulai; Mehdi Yaseri; Elham Shakibazadeh; Abolghassem Djazayery; Khadijeh Mirzaei (Wiley, 2021)
Abstract Introduction Psychological distress is a pervasive mental condition among persons with chronic noncommunicable diseases. Aim To examine whether interactions between patients' psychological distress and adherence to dietary recommendations predict glycemic controls among persons with type 2 diabetes mellitus in Ghana. Methods  Facility‐based cross‐sectional study involving 530 persons with type 2 diabetes mellitus was conducted between October 2018 and September 2019. Six health facilities were randomly selected and normal‐weight persons with type 2 diabetes mellitus (T2DM) at baseline consecutively recruited from patients' registers. Structured questionnaires were used to collect sociodemographic data. Glycemic control was the main outcome variable, and was determined using HbA1c%. Statistical Package for Social Sciences version 22 was used in data analysis. Results Systolic blood pressure (mm Hg), diastolic blood pressure (mm Hg), total cholesterol, and fasting blood sugar were statistically significant for glycemic control (HbA1c%) (p‐value < 0.05). After adjusting for confounding variables, low adherence and moderate adherence to dietary recommendations were independently significant for poor glycemic control (high HbA1c%). Interaction between low psychological distress and low adherence to dietary recommendations was statistically significant for poor glycemic control (high HbA1c%). Interaction between low psychological distress and moderate adherence to dietary recommendations was also statistically significant for poor glycemic control (high HbA1c%), whereas interaction between moderate psychological distress and high adherence to dietary recommendations was statistically significant for poor glycemic control (high HbA1c%). Conclusion Interaction between psychological distress and adherence to dietary recommendations can influence glycemic controls among persons with T2DM.